A comparative study on the right to maintenance under Civil and Muslim Law / Rosslin Peter Rosen - Peter Rosen, Rosslin (Faculty of Law, 1982)
The purpose of this paper is to make a comparative study on the right to maintenance under Civil and Muslim Law. This topic was chosen because of the writer’s interest in the law of maintenance while she did her practical training in Sarawak Legal Aid Bureau in Kuching after her second year of study in December, 1984. I t is aimed that this paper would bring out similarities and contrasts of the various laws in force in Malaysia governing the right of married women (and men) and children to maintenance and also the extent of the protection of this right. A marriage, being a civil contract regardless whether it is solemnised under Civil or Muslim Law, creates and imposes mutual rights and obligations. Maintaining a spouse and children of the marriage is one of the obligations imposed on spouses or parents. Different laws apply to different sets of people because of the legal history and different religions practised by the multi-racial population of Malaysia.